Collective impact approaches and community development issues. Issue 2 (14th March 2016) - Walzer, Norman; Weaver, Liz; McGuire, Catherine
Abstract: Efforts to accomplish successful results from community change processes have caused researchers and practitioners to develop new approaches to engage local resources in ways that can bring about positive community development outcomes. Collective impact (CI) as an approach has been shown to lead to sustained improvements and is gaining use around the world in working on community development concerns. This volume examines the application of CI to a variety of development issues and offers insights into approaches that seem to have generated positive and sustainable outcomes. Of special interest is the applicability of the techniques in different governmental settings and locations.